2015
DOI: 10.1111/jce.12623
|View full text |Cite
|
Sign up to set email alerts
|

Success Rates in Pediatric WPW Ablation Are Improved with 3‐Dimensional Mapping Systems Compared with Fluoroscopy Alone: A Multicenter Study

Abstract: Use of 3-D significantly improved success rates for ablation of WPW in children. The increase in acute success associated with 3-D suggests it is an important adjunct for catheter ablation of WPW in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
32
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 17 publications
2
32
0
Order By: Relevance
“…These cost savings described above likely also apply to 3D mapping, which is increasingly utilized in pediatric catheter ablations . Three‐dimensional mapping utilizes the same technique as conventional EP ablations regardless of whether three catheters or five catheters are used.…”
Section: Discussionmentioning
confidence: 99%
“…These cost savings described above likely also apply to 3D mapping, which is increasingly utilized in pediatric catheter ablations . Three‐dimensional mapping utilizes the same technique as conventional EP ablations regardless of whether three catheters or five catheters are used.…”
Section: Discussionmentioning
confidence: 99%
“…The use of fluoroscopy is also linked to a higher incidence of brain (particularly on the left side of the brain associated with proximity of x-ray machine) and neck tumors among electrophysiologists and other physicians performing interventional procedures (10). Also, ablation of accessory pathways with the aid of the 3D electro-anatomic mapping system has higher success rate compared to ablation done with fluoroscopy alone (97 % vs. 91 %) with no significant difference in recurrence (5 % vs. 9 %) or complication rate (0.3 % vs. 0.4 %) (11). Fluoroless ablation with the aid of the 3D electro-anatomic mapping system is thus a more attractive alternative for both, the patient and the physician.…”
Section: Discussionmentioning
confidence: 99%
“…With complication rates at ablation now far less than 1% and success rates with ablation for WPW approaching 97%, many practitioners and families have concluded that the risk/benefit ratio has tilted toward the side of invasive testing, risk assessment, and ablation [21,23,24]. The identifiable and notably small risk of invasive EP testing can then be weighed against the unknown but likely small, B) Baseline Exercise Fig.…”
Section: Role Of Isoproterenol Testingmentioning
confidence: 96%